2019
DOI: 10.32807/jgp.v4i2.135
|View full text |Cite
|
Sign up to set email alerts
|

Pengetahuan, Sikap Dan Personal Hygiene Tenaga Penjamah Makanan Di Ruang Pengolahan Makanan

Abstract: Background. According to Fatmawati, et al. (2013), one of the basic principles of organizing institutional food is the organization of foods that implement hygiene and sanitation in accordance with applicable regulations. One of the factors that support the principle of hygiene and sanitation in the provision of food is the factor of personal food hand hygiene. Personal hygiene is a clean, safe and healthy behavior of food handlers to prevent food contamination from food preparation to food serving. Some impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Researches by Lee et al, Alqurashi et al, Doraliyana et al revealed that personal hygiene is the most influential factor in food handlers regarding food quality [7], [32], [34]. Miranti and Adi research also support this and Assidiqi et al showed a relationship between knowledge and foodhandling hygiene [41], [42]. Research Lee et al demonstrated that food handlers have a good understanding of personal hygiene but not cross-contamination and sanitation because, in Malaysia, food handler training focuses more on personal hygiene than prevention cross-contamination pathogens [7].…”
Section: Attitude and Practice Knowledge Factormentioning
confidence: 84%
“…Researches by Lee et al, Alqurashi et al, Doraliyana et al revealed that personal hygiene is the most influential factor in food handlers regarding food quality [7], [32], [34]. Miranti and Adi research also support this and Assidiqi et al showed a relationship between knowledge and foodhandling hygiene [41], [42]. Research Lee et al demonstrated that food handlers have a good understanding of personal hygiene but not cross-contamination and sanitation because, in Malaysia, food handler training focuses more on personal hygiene than prevention cross-contamination pathogens [7].…”
Section: Attitude and Practice Knowledge Factormentioning
confidence: 84%
“…14 Hygiene perorangan merupakan perilaku bersih, aman dan sehat penjamah makanan untuk mencegah terjadinyakontaminasi pada makanan mulai dari persiapan hingga penyajian makanan. 15 Personal hygiene diperlukan baik orang sehat maupun pada orang sakit. Masalah kesehatan yang erat kaitannya dengan personal hygiene yaitu berupa kebersihan kulit rambut, kebersihan kuku tangan dan kaki, kebersihan kulit, kebersihan pakaian, kebersihan gigi dan mulut, dan perawatan tubuh secara keseluruhan.…”
Section: Pendahuluanunclassified
“…Penyelenggar aan makanan di rumah sakit dilaksanakan dengan tujuan untuk menyediakan makanan yang kualitasnya baik dan jumlah yang sesuai dengan kebutuhan serta pelayanan yang layak dan memadai bagi pasien yang menjalankan rawat inap. [10] Hygiene dan sanitasi mempunyai hubungan yang erat dan tidak dapat dipisahkan antara satu dengan yang lain. Higiene dan sanitasi merupakan usaha kesehatan masyarakat yang bertujuan untuk mencegah terjadinya penyakit pada manusia.…”
Section: Pendhuluanunclassified